Relationship Between Characteristics of Marine Debris and Impact to Coral Reef - Muhamad Gilang Arindra Putra; Neviaty Putri Zamani; Nyoman Metta Natih; Syawaludin Alisyahbana Harahap (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
HighlightMarine debris can be as a treat for coral reefBranching coral is the most affected by marine debrisPlastic marine debris commonly found in all research location, especially from fisheries and daily activityAbstractA coral reef is one of the important ecosystems, however, the existence of coral reef is threatened. Several factors can be a threat to the coral reef, such as marine debris. Research about marine debris on coral reefs in Indonesia has not much been done. This research aims to identify marine debris that is found and impacted, to identify the impacts caused, and to identify the life forms most susceptible to being affected. This research was conducted in Kelapa Island, Kelapa Dua Island, and Harapan Island by using the Belt Transect method sized 20 x 4 m2 with four repetitions at each station to determine coral reef life form, and type of marine debris. The data was analyzed by using the Correspondence Analysis (CA) to determine the correlation of marine debris and the affected life forms of coral reefs. The result showed the plastic marine debris was found in all stations. Six life forms were affected by marine debris, and the most susceptible life forms that affected were massive and branching. The most dominant impact category on coral reefs was tissue loss with algal growth (TLAG).